Religion, foreign policy and populism in Turkish politics: introducing a new framework. Issue 4 (19th May 2021) - Bulut, Alper T.; Hacıoğlu, Nurhan
ABSTRACT: By content-coding 40 parliamentary group speeches of the major Turkish parties over a period of 4 years, we show that existing measures of populism should include two more categories in order to understand the populist communication strategies of the Turkish political parties. The first category is "discursive religious symbolism" which is included in the thin populism dimension. The other is "foreign policy populism" which is included in the thick populism dimension. Our results show that the inclusion of these new categories is crucial for our understanding of populist communication styles in Turkish politics. The results also indicate that both discursive religious symbolism and foreign policy populism plays a crucial role in the resilience of the incumbent Justice and Development Party.